THE EFFORTS TO INCREASE STUDENTS’ SELF-CONFIDENCE THROUGH THEATER LEARNING IN ELEMENTARY SCHOOL - fauziah; Astri Sutisnawati; Irna Khaleda Nurmeta (Jurnal Cakrawala Pendas, 2024)
Character education is an important aspect of forming a quality personality. In the educational context, learning methods are needed that aim to optimise the development of a person's abilities in character development at the elementary school level. This study aims to describe the implementation of theater learning and identify how theater learning can improve students' self-confident character. This research uses the Classroom Action Research (CAR) method consisting of two cycles. Each cycle begins with planning, implementation, observation, and reflection. The instruments used include teacher observation sheets, student observation sheets and pre-tests in the form of performance. The results show that theater learning in elementary schools can improve students’ self-confident. This can be seen from the data obtained in Cycle I, namely that 17 out of 30 students or approximately 56,6% had self-confidence with an average score of 57,7. Meanwhile in Cycle II all students showed an increase in self-confidence, with an average score of 81,6.